Pathological evaluation of tumor grade for salivary adenoid cystic carcinoma: A proposal of an objective grading system. Issue 3 (2nd February 2021) - Morita, Naruhiko; Murase, Takayuki; Ueda, Kaori; Nagao, Toshitaka; Kusafuka, Kimihide; Nakaguro, Masato; Urano, Makoto; Taguchi, Ken‐ichi; Yamamoto, Hidetaka; Kano, Satoshi; Tada, Yuichiro; Tsukahara, Kiyoaki; et al.
Abstract: Three pathological grading systems advocated by Perzin/Szanto, Spiro, and van Weert are currently used for adenoid cystic carcinoma (AdCC). In these systems, the amount or presence of the solid tumor component in AdCC specimens is an important index. However, the "solid tumor component" has not been well defined. Salivary AdCC cases (N = 195) were collected after a central pathology review. We introduced a novel criterion for solid tumor component, minAmax (min or a xis max imum). The largest solid tumor nest in each AdCC case was histologically screened, the maximum oval fitting the solid nest was estimated, and the length of the minor axis of the oval (minAmax) was measured. The prognostic cutoff for the minAmax was determined using training and validation cohorts. All cases were evaluated for the four grading systems, and their prognostic impact and interobserver variability were examined. The cutoff value for the minAmax was set at 0.20 mm. Multivariate prognostic analyses showed the minAmax and van Weert systems to be independent prognostic tools for overall, disease‐free, and distant metastasis‐free survival while the Perzin/Szanto and Spiro systems were selected for overall survival but not for disease‐free or distant metastasis‐free survival. The highest hazard ratio for overall survival (11.9) was obtained with the minAmax system. The reproducibility of the minAmax system (kappa coefficient of 0.81) was scored as very good while those of the other three systems were scored as moderate. In conclusion, the minAmax is a simple, objective, and highly reproducible grading system useful for prognostic stratification for salivary AdCC. Abstract : The amount or presence of the solid tumor component is an important index for histopathological grading of adenoid cystic carcinoma. However, the "solid tumor component" has not been well defined. We introduced a novel objective criterion for solid tumor component, minAmax (minor axis maximum), and showed that the minAmax is a simple, objective, and highly reproducible grading system useful for prognostic stratification for salivary adenoid cystic carcinoma.